التعليم الجامعي الاهلي واقعه ودوره وسبل النهوض به (Journal Of Educational and Psychological Researches, 2017)
The research aims to acquaint the reality of Privet universities education in Iraq and acquaint of its role and ways to promote it. The research contains three chapters, the First Chapter includes The Importance of Research, the need of the research, the goals of the research and its borders. The Second Chapter handles with The Historical Scope of Privet universities education in Iraq and most important previous studies that deal with this topic. The Third Chapter deals with The Reality of Community Privet Universities in Iraq through scientific composure, scientific level of the students admitted in privet education between planning and marketing research and then take main issues of privet universities education and ways to solve these issues. At the end, complete the research with a few instructions as following: 1- Making studies to measure the capacity of the educational activity of the privet colleges in the country, their levels and to determine the indicators of actual performance of these colleges in the field of education and field of scientific. 2- Work on the applying of international quality standards due to its positive effects on the various activities in the community colleges. 3- It is necessary to give private universities some independence to choose curriculum syllabus that adequate with the privacy of these universities. 4- Privet colleges follow-up development of the current and the projected design curricula and academic vocabulary of the labor market in the light of these developments.